Ginkgo biloba for prevention of acute mountain sickness: Does it work? - Tissot van Patot, M. C.; Keyes, L. E.; Leadbetter III, G.; Hackett, P. H. (High Altitude Medicine & Biology, 2009)
We review the current literature regarding the prophylactic use of Ginkgo biloba extract (GBE) in acute mountain sickness (AMS). We compare studies with regard to GBE dose, composition, study design, altitude reached, ascent rate, exercise, and risk of AMS. We then review what is known about the active components of GBE and their biological effects and apply this knowledge to interpret the results of AMS prevention trials. Overall, the literature suggests that due to the complexity of GBE the standardization of the product is inadequate, which likely explains the disparate clinical results. The variability in commercially available GBE products makes it impossible to determine whether GBE is truly effective for preventing or ameliorating AMS. However, investigating the roles of specific active components of GBE in the prevention of AMS could yield rewards both clinically and in our understanding of the pathophysiology of AMS.